2000
DOI: 10.14430/arctic848
|View full text |Cite
|
Sign up to set email alerts
|

Radionuclide Contaminant Burdens in Arctic Marine Mammals Harvested During Subsistence Hunting

Abstract: ABSTRACT. We conducted gamma spectrometric analyses on more than 200 arctic marine mammal tissue samples. These samples were primarily provided by subsistence hunters from northern Alaska, with a smaller number of samples from the Resolute region in Canada. The majority of samples (>90%) had detectable levels of the anthropogenic radionuclide 137 Cs, with a mean level observed in all samples of 0.67 Bq kg -1 dry weight ± 0.81 (SD). Converted to wet weight, the mean was 0.21 Bq kg -1 ± 0.19 SD. The median activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 31 publications
2
8
0
Order By: Relevance
“…However, it would appear from our data that these potential sources currently have little impact on marine mammals in the European Arctic. Cooper et al, (2000) reported average 137 Cs activities in muscle samples for a variety of marine mammal species from Alaska and Canada, including polar bears, ringed seals and bearded seals that were similar to those seen in this study and other studies done in the European Arctic. The global distribution of radionuclide contamination in marine mammals shows that values are generally higher in the northern hemisphere than in the southern.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…However, it would appear from our data that these potential sources currently have little impact on marine mammals in the European Arctic. Cooper et al, (2000) reported average 137 Cs activities in muscle samples for a variety of marine mammal species from Alaska and Canada, including polar bears, ringed seals and bearded seals that were similar to those seen in this study and other studies done in the European Arctic. The global distribution of radionuclide contamination in marine mammals shows that values are generally higher in the northern hemisphere than in the southern.…”
Section: Discussionsupporting
confidence: 86%
“…Additionally, due to the subsistence harvesting of some marine mammals by arctic indigenous peoples there is a need for information on current radionuclide burdens, so that accurate assessments can be made concerning potential doses to man. Cooper et al (2000) reported radionuclide contaminant burdens for several marine mammals in northern Alaska and Canada to be low. Similar species-specific data in the literature for marine mammals in the European Arctic is scarce.…”
Section: Introductionmentioning
confidence: 99%
“…This has arisen because of a requirement to provide analogues for protected species within Europe, as these are often the types of biota for which assessments are required (Copplestone et al, 2003). Furthermore, the geometric components of the original FASSET reference organism have been replaced by related ICRP Reference Animals and Plants (RAPs) where the similarity justifies this procedure.…”
Section: Expanded List Of Reference Organisms and Radioelementsmentioning
confidence: 99%
“…The first three options were used as preferential approaches. The main sources of information for Code 3 (CR values recommended in previous reviews or derived from previously published reviews) were IAEA (2001) and Copplestone et al (2003). Options 4 and 6e8 were not applied for freshwater organisms.…”
Section: Freshwatermentioning
confidence: 99%
“…Thus, data are available from other regions, including the Arctic, Asian and European coastal waters, Lake Baikal and the Caspian and Black Seas. These studies reported average levels of 137 Cs that varied between 0.2 and 17 Bq kg −1 wet weight (w.w.) (Cooper et al, 2000;Yoshitome et al, 2003;Gwynn et al, 2005;Andersen et al, 2006;Malta & Carvalho, 2011). Cesium-137 levels in tissues of marine mammals have been suggested as chemical marker for radioactive pollution in the marine environment, and correlations between tissue levels and seawater levels have been reported (Yoshitome et al, 2003).…”
mentioning
confidence: 99%